Предмет: Математика,
автор: Stanley07
помогите пожалуйста разобраться.
(27*4)^1/6-3^1/2*2^1/3
Ответы
Автор ответа:
0
(27*4)^(1/6) - 3^(3/6)*2^(2/6)=
=(3^3*2^2)^(1/6) - 3^(3/6)*2^(2/6)=
=3^(3/6)*2^(2/6) - 3^(3/6)*2^(2/6)=0
=(3^3*2^2)^(1/6) - 3^(3/6)*2^(2/6)=
=3^(3/6)*2^(2/6) - 3^(3/6)*2^(2/6)=0
Автор ответа:
0
1) 27 = 3^3
2) 4 = 2^2
3) (3^3 * 2^2)^16 = 3^(3*16) * 2^(2*16) = 3^12 * 2^13
4) 3^12*2^13 - 3^12*2^13 = 0
Похожие вопросы
Предмет: Математика,
автор: svetavisnevskay
Предмет: География,
автор: sasha2005martyk16
Предмет: Математика,
автор: kamila090617
Предмет: География,
автор: akassy1